Effects of pulsing current and filler materials on the mechanical and metallurgical properties of DSS 2205 weldments. Issue 1 (April 2021) - Sathishkumar, M; Nagpal, Sawan; Gupta, Harshit; Bhargava, Sanjalp; Reddy, S A Nithin Joseph; Kumar, K Gokul; Manikandan, M; Arivazhagan, N
Abstract: The control of balance in austenite to ferrite ratio of duplex stainless steel (2205) during welding is critical due to not choosing the optimum heat input and cooling rate and welding processes, which leads to the development of embrittlement of intermetallic precipitates in the weldment. Further, the imbalance of austenite to ferrite ratio primes the stress corrosion cracking (ferrite < 25 %), low impact toughness and corrosion resistance (ferrite > 75 %). The pulse current gas tungsten arc (PCGTA) welding has utilized to weld the DSS 2205 using ERNiCrMo-3 and ERNiCrMo-4 fillers for better control of austenite to ferrite ratio. The tensile strength of Mo-3 weldment is 4.06 % higher than Mo-4. Besides, the Mo-3 weldment also provided the enhanced impact toughness and microhardness compared to Mo-4. The macrographs show similar weld bead width. The microstructure of both fillers Mo-3 & Mo-4 confirmed columnar structure at the weld interface and the finer equiaxed structure at weld center. The scanning electron microscope along with energy dispersive spectroscopy assured the absence of Cr2N, Chi and sigma phases. The PCGTA of DSS 2205 with Mo-3 is giving the improved properties with respect to Mo-4.